Optimal Tasks Assignment for Multiple Heterogeneous Processors with Dynamic Re-assignment - Kumar, Harendra; Singh, M. P.; Yadav, Pradeep Kumar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Distributed Computing System [DCS] has attracted several researchers by posing several challenging problems. In this paper we have developed a mathematical model for allocating â€œMâ€ tasks of distributed program to â€œNâ€ multiple processors (M>N) that minimizes the total cost of the program. Relocating the tasks from one processor to another at certain points during the course of execution of the program that contributes to the total cost of the running program has been taken into account. Most of the researchers have considered the cost for relocating the task from one processor to another processor at the end of the phase as a constant. But in real life situations the reallocating cost of the tasks may very processor to processor this is due to the execution efficiency of the processors. Phase-wise execution cost [EC], inter task communication cost [ITCT], residence cost [RC] of each task on different processors and relocation cost [REC] for each task have been considered while preparing a dynamic tasks allocation model.